Evidence-based sustainable business model design for agrifood side-stream biostimulants - Federico Zilia; Luca Ferraro; Jacopo Bacenetti; Luigi Orsi (PLoS ONE, 2026)
Circular bioeconomy initiatives often valorise food-processing residues into bio-based inputs, yet environmental gains depend on how technologies are implemented and governed across multiple actors. This study evaluates a pathway that converts leek processing residues into a bioactive extract used as a plant biostimulant in greenhouse lettuce production and develops an evidence-based procedure to design a sustainable business model around it. We conducted a cradle-to-gate Life-Cycle Assessment (LCA) of leek extract production and a comparative LCA of lettuce cultivation for a baseline system and an alternative system applying the extract, using the Environmental Footprint (EF) 3.1 midpoint indicators. The alternative scenario improved most indicators, with consistent reductions in acidification, eutrophication and freshwater ecotoxicity, while selected trade-offs were associated with the upstream extract supply chain, particularly in resource-related and process-sensitive impact categories. We then embedded these multi-impact hotspot signals into an ecosystem-oriented Sustainable Business Model Canvas (SBMC) and an experimentation logic, specifying who must act on each hotspot (processors, extract producers, labs, farmers) and how mitigation and verification can be financed through value capture (product-service bundles, monitoring, and conditional sustainability claims). The approach links LCA evidence to actionable business model choices, supporting credible scaling of residue-based agrifood innovations.